2011
DOI: 10.1371/journal.pone.0021662
|View full text |Cite
|
Sign up to set email alerts
|

Offspring of Mothers Fed a High Fat Diet Display Hepatic Cell Cycle Inhibition and Associated Changes in Gene Expression and DNA Methylation

Abstract: The association between an adverse early life environment and increased susceptibility to later-life metabolic disorders such as obesity, type 2 diabetes and cardiovascular disease is described by the developmental origins of health and disease hypothesis. Employing a rat model of maternal high fat (MHF) nutrition, we recently reported that offspring born to MHF mothers are small at birth and develop a postnatal phenotype that closely resembles that of the human metabolic syndrome. Livers of offspring born to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(105 citation statements)
references
References 39 publications
7
96
1
1
Order By: Relevance
“…The nutritional regulation on the epigenome during liver development is very limited. HF diets had been shown to mediate DNA methylation at specific CpG sites on the promoter of gene and affected gene expression, thereby leading to physiological alterations (4,7,10,11,18,29). A recent study that applied Illumina's Infinium Bead Array assessed at 27,578 CpG sites associated with 14,475 genes has shown that a short-term feeding of HF diet induced genome-wide DNA methylation change at CpG sites in the skeletal muscle of healthy young men (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nutritional regulation on the epigenome during liver development is very limited. HF diets had been shown to mediate DNA methylation at specific CpG sites on the promoter of gene and affected gene expression, thereby leading to physiological alterations (4,7,10,11,18,29). A recent study that applied Illumina's Infinium Bead Array assessed at 27,578 CpG sites associated with 14,475 genes has shown that a short-term feeding of HF diet induced genome-wide DNA methylation change at CpG sites in the skeletal muscle of healthy young men (17).…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of these genes is primarily associated with aberrant hepatic lipid and glucose metabolism, resulting in the development of various types of noncommunicable diseases, including fatty liver disease and obesity. Additionally, alterations of DNA methylation patterns of cell cycle controlled gene Cdkn1a (10) and growth hormone secretagogue receptor (11) were reported in offspring of a maternal HF model, implying the transgenerational epigenetic effects of HF diet. Correlation of DNA methylation and gene expression has been validated in many of these studies, indicating that the HF diet affects gene regulations through alterations of DNA methylation of particular genes.…”
mentioning
confidence: 99%
“…Epigenetics comprises, among other more technically challenging methods, the investigation of DNA methylation profiles as the primary mark of environmentally mediated changes to gene expression. While the exact role of epigenetic mechanisms in fetal programming of metabolic diseases and body weight regulation remains to be further investigated, a number of animal models have demonstrated a causal relationship between early nutrition and later metabolic phenotype with gene dysregulation mediating such adverse metabolic outcomes (58)(59)(60)(61)(62) . A recently published article reviews the scientific evidence base of the association between the role of epigenetics in the fetal programming of adverse metabolic outcomes concluding that despite a vast amount of epigenomic data generated, the challenge still is to decipher the biological and clinical relevance of these epigenetic changes (63) .…”
Section: Epigenetics and Metabolomicsmentioning
confidence: 99%
“…Again, epigenetic processes probably play a role. Experiments in rats show epigenetic changes in the livers of o spring of dams fed a high-fat diet (32). Children of mothers with gestational diabetes mellitus (GDM)-diabetes that appears during pregnancy and then resolves a er pregnancy-have a greater propensity to develop type 2 diabetes as adults.…”
Section: Biological Determinantsmentioning
confidence: 99%